The Analysis of Word Formation in Coffee Shops’ Menus in Bintaro - Maharini, May Triranto; Nainggolan, Erni Susianti (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study aims to find the word formation employed in coffee shop menus in Bintaro, Tangerang, Indonesia. By examining word formation processes, naming conventions, and menu item types. This research aims to understand how coffee shops effectively communicate their offerings to customers through word formation processes. It adopts a qualitative research approach, utilizing purposive sampling to select representative coffee shops in the area. Through in-person visits and online sources, menus were collected and analyzed for their linguistic features. The findings reveal that coffee shops in Bintaro utilize word formation processes. Compounding involves combining two or more words to create a new term, such as